2021
DOI: 10.3389/fcell.2021.654885
|View full text |Cite
|
Sign up to set email alerts
|

Translational Animal Models Provide Insight Into Mesenchymal Stromal Cell (MSC) Secretome Therapy

Abstract: The therapeutic potential of the mesenchymal stromal cell (MSC) secretome, consisting of all molecules secreted by MSCs, is intensively studied. MSCs can be readily isolated, expanded, and manipulated in culture, and few people argue with the ethics of their collection. Despite promising pre-clinical studies, most MSC secretome-based therapies have not been implemented in human medicine, in part because the complexity of bioactive factors secreted by MSCs is not completely understood. In addition, the MSC secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 216 publications
(209 reference statements)
0
32
0
Order By: Relevance
“…MSCs exert their functions through the secretome, including soluble proteins, nucleic acids, and lipids, which show similar effects to those MSCs. 39 , 40 Therefore, we next investigated whether PO-MSCs promoted EMT and epithelial barrier destruction in pHNECs by secreted proteins, including IGFBP2, matrix metalloproteinase 9 (MMP9), monocyte chemotactic protein-1 (MCP-1), vascular endothelial growth factor A (VEGFA) and interleukin-1β (IL-1β), all of which are associated with pathogenic biological behaviors. 26 , 41 , 42 Remarkably, compared with mock control and PO-MSCs-EVs, only IGFBP2 was significantly enriched in PO-MSCs-CM ( Figure 5 A).…”
Section: Resultsmentioning
confidence: 99%
“…MSCs exert their functions through the secretome, including soluble proteins, nucleic acids, and lipids, which show similar effects to those MSCs. 39 , 40 Therefore, we next investigated whether PO-MSCs promoted EMT and epithelial barrier destruction in pHNECs by secreted proteins, including IGFBP2, matrix metalloproteinase 9 (MMP9), monocyte chemotactic protein-1 (MCP-1), vascular endothelial growth factor A (VEGFA) and interleukin-1β (IL-1β), all of which are associated with pathogenic biological behaviors. 26 , 41 , 42 Remarkably, compared with mock control and PO-MSCs-EVs, only IGFBP2 was significantly enriched in PO-MSCs-CM ( Figure 5 A).…”
Section: Resultsmentioning
confidence: 99%
“…These promising compounds are currently being tested in combination with standard chemotherapy or allogenic transplantation settings in clinical trials of high-risk MDS and refractory AML patients ( Martínez-Cuadrón et al, 2018 ; Roboz et al, 2018 ; Michelis et al, 2019 ; Bose et al, 2020 ). On the other hand, the anti-tumoral effects displayed by MSCs were attributed to small secreted factors ( Maguire, 2013 ; Moll et al, 2020 ; Wu et al, 2020 ) and led to increased interest in the use of MSC secretome for anti-leukemic therapy as well as for a wide array of other diseases, such as ischemic, neuroinflammatory and pulmonary malignancies (reviewed in Harman et al, 2021 ). Collective proteomic studies demonstrated that the MSC secretome consists of trophic factors (e.g., FGF, HGF, VEGF), cytokines (e.g., IL-6, TGFβ-1…), hormones, small peptides (e.g., SCF, PTG, Leptin) and extracellular vesicles (EVs) containing miRNA, mRNA and biologically active proteins ( Chulpanova et al, 2018 ).…”
Section: Msc Heterogeneity In Myeloid Malignanciesmentioning
confidence: 99%
“…The most concerning are 3D culture, hypoxia, genetic engineering, cytokine pretreatment, etc. [ 10 , 11 ]. Previous studies have verified that stem cell preconditioning could dynamically alter the composition of their secretome.…”
Section: Introductionmentioning
confidence: 99%